Synthesis, Biophysical Properties, and Antitumor Activity of Antisense Oligonucleotides Conjugated with Anisamide - Zhe Zhang; Zuyi Chen; Cheng Li; Zhenyu Xiao; Yuan Luo; Xiaochen Pan; Liang Xu; Xuesong Feng (MDPI AG, 2023)
Antisense oligonucleotides (ASONs) have proven potential for the treatment of various diseases. However, their limited bioavailability restricts their clinical application. New structures with improved enzyme resistance stability and efficient drug delivery are needed. In this work, we propose a novel category of ASONs bearing anisamide conjugation at phosphorothioate sites for oncotherapy. ASONs can be conjugated with the ligand anisamide very efficiently and flexibly in a solution. The conjugation sites and the ligand amount both influence anti-enzymatic stability and cellular uptake, resulting in changes in antitumor activity that are detectable by cytotoxicity assay. The conjugate with double anisamide (T6) was identified as the optimal conjugate, and its antitumor activity and the underlying mechanism were examined further in vitro and in vivo. This paper presents a new strategy for the design of nucleic acid-based therapeutics with improved drug delivery and biophysical and biological efficacy.